25 years of the TETRA standard and technology for contemporary digital trunking systems of professional mobile radio communications - Svrzić, Slađan M. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: For the construction of functional mobile radio communication systems today, the trunking systems of digital mobile radio communications are almost exclusively used, the main representative of which is the system with the application of TETRA standards. This article describes the beginnings and historical development of this standard, with the activities of ETSI and TETRA MoU in the fight for the availability and harmonization of the frequency spectrum.Methods: A description of relevant issues of the origin and development of the TETRA 1 standard is given as well as the analysis of the characteristic moments of the innovated TETRA 2 standard.Results: This article describes the beginnings and historical development of this standard, with the activities of ETSI and TETRA MoU in the fight for the availability and harmonization of the frequency spectrum. It also systematize the use of the key TETRA systems in the world and shows its share in the world market by sectors, emphasizing the dilemma of its further development at the crossroads after 25 years of existence. Also, a basic overview of the TETRA 1 standard is given while the basic elements and the principle of its application are described. The innovated TETRA 2 standard and the improvements achieved in the way of data transmission are described in more detail; the process of interoperability certification and, in connection with that, the entry of TETRA into the North American market is emphasized. The parameters selected for advanced data transfer according to the TETRA 2-TEDS standard are presented and analyzed, together with an overview of some limitations during practical application.Conclusion: In the conclusion, the current moment of TETRA is analyzed with a focus on its future after 25 years of development, emohasizing a possibility of modernizing and improving the TETRA network of the Ministry of the Interior of Serbia for the needs of the MoD and the Serbian Armed Forces.
Keywords: mobile radio communications-MR; public mobile radio communication system-PAMR; professional mobile radio communication system-PMR; area-interface-AI; digital trunking system of mobile radio communications-TETRA; TETRA enhanced data service-TEDS; European telecommunications standardization institute-ETSI